E-COMMERCE DIFFERENCES BETWEEN DEVELOPING AND DEVELOPED COUNTRIES (Marketing Journal, 2025)
E-commerce is a huge component of the digital economy as the business market landscape is now based on digital competition. E -commerce assists with national development through the creation of jobs and import tax. However, developing countries are lagging in e -commerce adoption due to internet challenges, trust, and security issues about online payment facilities. Despite these challenges, this study aimed at understanding the factors influencing e -commerce adopti on in developing countries. The factors are built from the benefits and challenges of adoption. To address the research aim, the study identified the challenges and benefits of e -commerce adoption in developing countries using a systematic literature review methodology.
Keywords: s: digitalisation; e -commerce; market competition; infrastructure; challenges; global economies; developed countries; buying and selling; economic growth